PENGELOLAAN PAJAK BUMI DAN BANGUNAN PERDESAAN DAN PERKOTAAN - Ocdelina, Silvia; Heriyanto, Meyzi; Farida, Lena (Jurnal Ilmu Administrasi Negara, 2019)
Management of Rural and Urban Land and Building Taxes: This study aims to know management of rurar and urban land and building taxes of of Siak Regency in 2011-2015. Type of Research which is a qualitative approach. Qualitative data which is the result of interviews and a list of research objects. The data obtained is then analyzed through organizing data, translated into units, compiled into patterns, choosing which data is important and which will be studied, elaborating in the form of words and sentences and as long as making conclusions. Research informants were section, intensification, extensification and billing sections. The results of the study indicate that the PBB P2 which cannot be said maximal because there are still intersecting, among others update database, inadequate Human Resources and facilities that have not accommodated PBB P2.